2015
DOI: 10.1002/hbm.22801
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis of neuroimaging studies on divergent thinking using activation likelihood estimation

Abstract: In this study, an activation likelihood estimation (ALE) meta-analysis was used to conduct a quantitative investigation of neuroimaging studies on divergent thinking. Based on the ALE results, the functional magnetic resonance imaging (fMRI) studies showed that distributed brain regions were more active under divergent thinking tasks (DTTs) than those under control tasks, but a large portion of the brain regions were deactivated. The ALE results indicated that the brain networks of the creative idea generation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
111
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(129 citation statements)
references
References 92 publications
10
111
2
1
Order By: Relevance
“…The left IFG has previously been implicated in fMRI studies using the verb generation task (Crescentini et al, 2010; Thompson-Schill, 2003), and it has shown consistent activation in neuroimaging studies of creative cognition (Gonen-Yaacovi et al, 2013; Wu et al, 2015). A substantial body of evidence has shown that the left IFG supports semantic retrieval processes, particularly during cognitive tasks involving the search and selection of target concepts among a large set of competing alternatives (Crescentini et al, 2010; Grindrod et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The left IFG has previously been implicated in fMRI studies using the verb generation task (Crescentini et al, 2010; Thompson-Schill, 2003), and it has shown consistent activation in neuroimaging studies of creative cognition (Gonen-Yaacovi et al, 2013; Wu et al, 2015). A substantial body of evidence has shown that the left IFG supports semantic retrieval processes, particularly during cognitive tasks involving the search and selection of target concepts among a large set of competing alternatives (Crescentini et al, 2010; Grindrod et al, 2008).…”
Section: Discussionmentioning
confidence: 88%
“…The dorsolateral prefrontal cortex (DLPFC), for example, has been implicated in studies of general creative cognitive processing (Chen et al, in press; Gonen-Yaacovi et al, 2013; Wu et al, 2015) and artistic performance (Beaty, 2015; Boccia et al, 2015; Pinho et al, 2014, 2016). DLPFC activation during creative task performance is thought to reflect the involvement of executive control processes (Beaty et al, 2016; Benedek et al, 2014a; Chen et al, 2015, in press).…”
Section: Neurocognitive Mechanisms Supporting Creative Idea Productionmentioning
confidence: 99%
“…Precuneus activity is thought to be associated with self-referential thought (Cavanna and Trimble 2006) and this activity must be suppressed in order to exert effortful control over behavior (Raichle et al 2001). Likewise, deactivation of the SMG (BA 40) may be related to inhibition of irrelevant cognitive processes (Fink et al 2009; Wu et al 2015). Therefore, we speculate that the stress-induced increase in BOLD signal change in the SMG, IFG, and Precuneus may be attributed to difficulty suppressing intrusive thoughts as a result of negative feedback during the stress condition.…”
Section: Discussionmentioning
confidence: 99%
“…[52]). Although memory retrieval appears to play an important role in idea generation, cognitive control systems can also be recruited to evaluate and modify candidate ideas to meet specific goals, in line with behavioral [5359] and neuroimaging [37, 6064] evidence showing consistent involvement of executive mechanisms in creative thought. Thus, the control and default networks may cooperate to leverage both top-down (executive) and bottom-up (generative) processes during creative cognition.…”
Section: Brain Network and Creative Cognition: An Integrative Frameworkmentioning
confidence: 99%